2020
DOI: 10.1074/jbc.ra120.015020
|View full text |Cite
|
Sign up to set email alerts
|

GGPP depletion initiates metaflammation through disequilibrating CYB5R3-dependent eicosanoid metabolism

Abstract: Metaflammation is a primary inflammatory complication of metabolic disorders characterized by altered production of many inflammatory cytokines, adipokines and lipid mediators. While multiple inflammation networks have been identified, the mechanisms by which metaflammation is initiated have long been controversial. As mevalonate pathway (MVA) produces abundant bioactive isoprenoids and abnormal MVA has a phenotypic association with inflammation/immunity, we speculate that isoprenoids from the MVA may provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…CYB5R2 localizes in the Golgi apparatus and nucleoplasm and is highly expressed in the testis. In CYB5R3-overexpressing H1299 cells, CYB5R3 was mainly located in the ER and undergoes posttranslational modi cations, leading to changes in subcellular localization [40][41][42] . Recent studies have suggested that prenylated CYB5R3 translocates from the mitochondria to the ER, while non-prenylated CYB5R3 localizes in the mitochondria 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYB5R2 localizes in the Golgi apparatus and nucleoplasm and is highly expressed in the testis. In CYB5R3-overexpressing H1299 cells, CYB5R3 was mainly located in the ER and undergoes posttranslational modi cations, leading to changes in subcellular localization [40][41][42] . Recent studies have suggested that prenylated CYB5R3 translocates from the mitochondria to the ER, while non-prenylated CYB5R3 localizes in the mitochondria 41 .…”
Section: Discussionmentioning
confidence: 99%
“…In CYB5R3-overexpressing H1299 cells, CYB5R3 was mainly located in the ER and undergoes posttranslational modi cations, leading to changes in subcellular localization [40][41][42] . Recent studies have suggested that prenylated CYB5R3 translocates from the mitochondria to the ER, while non-prenylated CYB5R3 localizes in the mitochondria 41 . In particular, geranylgeranyl diphosphate synthase (GGPPS), which is involved in CYB5R3 prenylation, is overexpressed in lung adenocarcinoma 40 .…”
Section: Discussionmentioning
confidence: 99%
“…q-PCR assay Quantitative RT-PCR was performed, as described previously (56,57). Total RNA was extracted from the tissues using RNAiso Plus (9109, Takara Bio) according to the manufacturer's instructions.…”
Section: Preparation Of Conditioned Mediummentioning
confidence: 99%
“…Isoprenoid geranylgeranyl diphosphate (GGPP) is a crucial intermediator in the mevalonate pathway (MVA) for cholesterol, terpene, and terpenoid synthesis, which mainly occurred in the liver [18,19]. GGPP is involved in protein prenylation, a post-translational modification essential for the functioning of many peripheral and signal transduction proteins containing cysteine residues in the CaaX motif, such as SREBP1 and CYB5R3 [20,21].…”
Section: Introductionmentioning
confidence: 99%